Digital Transformation of Madrasah in the 5.0 Society Era - Asma’ul Husna; Rusdarti Rusdarti; Haryono Haryono; Ali Formen (Universitas Negeri Semarang, 2023)
The era of society 5.0 which is characterized by the presence of digital evolution in the form of Artificial Intelligence (AI), Internet of Things (IoT), and robotics requires the education system to be able to adapt in order to keep up with the times, including madrasah as a formal Islamic education system. Some of the problems faced by madrasahs in the society era 5.0 include the low understanding of madrasah human resources technology, as well as services and curriculum that are not yet digitally oriented. For this reason, it is necessary to innovate in the form of digital transformation of madrasahs in facing developments in the society era 5.0. This development innovation design is a literature study with SWOT analysis. The innovation design offered is in the form of digital transformation of madrasah internally and externally, namely by digitizing services and curriculum, as well as increasing the understanding of madrasah HR technology. As for externally, digital transformation is in the form of output produced by utilizing digitalization in the form of madrasah branding in the form of digital marketing, as well as a medium for da'wah.